Antimutagenic and anticlastogenic effects of Turkish Black Tea on TA98 and TA100 strains of Salmonella typhimurium (in vitro) and mice (in vivo). (1st January 2017) - Charehsaz, Mohammad; Sipahi, Hande; Giri, Ashok Kumar; Aydin, Ahmet
Abstract: Context: Black tea has been reported to have significant antimutagenic and anticarcinogenic properties associated with its polyphenols theaflavins (TF) and thearubigins (TR). Similarly, Turkish black tea (TBT) also contains a considerable amount of TF and TR. Objective: This study investigated the mutagenic, antimutagenic and anticlastogenic properties of TBT. Materials and methods: The mutagenic and antimutagenic effects of TBT (10 to 40000 μg/plate) were investigated in vitro on Salmonella strains TA98 and TA100 with and without S9 fraction. Anticlastogenic effect was studied at concentrations of 300–1200 mg/kg TBT extract by chromosomal aberrations (CA) assay from bone marrow of mice. Results: The results of this study did not reveal any mutagenic properties of TBT. On the contrary, TBT extract exhibited antimutagenic activity at >1000 μg/plate concentrations in TA98 strain with and without S9 activation (40% inhibition with S9 and 27% without S9). In TA100 strain, the antimutagenic activity was observed at >20, 000 μg/plate TBT extracts without S9 activation (28% inhibition) and at >1000 μg/plate with S9 activation (59% inhibition). A significant decrease in the percentage of aberrant cells (12.33% ± 1.27) was observed in dimethylbenz( a )anthracene (DMBA) plus highest concentration (1200 mg/kg) of TBT extract-treated group when compared to only DMBA-treated group (17.00% ± 2.28). Discussion and conclusion: Results indicated that TBT can be considered as genotoxically safe, because it did not exert any mutagenic and clastogenic effects. As a result, TBT exhibited antimutagenic effects more apparently after metabolic activation in bacterial test system and had an anticlastogenic effect in mice.